2020
DOI: 10.1021/acsanm.0c00383
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Nanoparticles Supported on Mg(OH)2 Microflowers as Catalysts for Photothermal Carbon Dioxide Hydrogenation

Abstract: A strong sunlight-absorptive ability and high dispersity are considered as two key requirements of supported metal catalysts for efficient photothermal CO 2 conversions. The former can be improved by increasing the metal loading but often at the expense of decreasing the latter. Here we develop an ion-exchange route to supported Ru nanoparticles with both high loadings and dispersity that exhibit enhanced activity and relatively good stability in photothermal CO 2 catalysis. This strategy involves an ionexchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 56 publications
1
23
0
1
Order By: Relevance
“…Through an ion-exchange method Ru was incorporated in a Mg(OH) 2 support with a three-dimensional nanoflower structure followed by 150 1C H 2 -reduction to create the metallic Ru. 193 therefore suggesting that thermocatalysis rules the photo-thermal reaction. Anyway, deeper investigations must be done to explain the photo-thermal effects and mechanisms but it is obvious that a suitable amount and dispersion of Ru increase the light absorption and can modify the product distribution, defining these variables as key factors in photo-thermal CO 2 reduction.…”
mentioning
confidence: 99%
“…Through an ion-exchange method Ru was incorporated in a Mg(OH) 2 support with a three-dimensional nanoflower structure followed by 150 1C H 2 -reduction to create the metallic Ru. 193 therefore suggesting that thermocatalysis rules the photo-thermal reaction. Anyway, deeper investigations must be done to explain the photo-thermal effects and mechanisms but it is obvious that a suitable amount and dispersion of Ru increase the light absorption and can modify the product distribution, defining these variables as key factors in photo-thermal CO 2 reduction.…”
mentioning
confidence: 99%
“…The photothermal catalysis couples the photocatalytic and thermocatalytic processes, and both of them play key roles in activating reactant molecules and tuning the status of reaction intermediates and determining the conversion direction, instead of an energy conversion between photoenergy and thermal energy, which enhances the catalytic performance (activity and selectivity) for various catalytic transformations. [53][54][55][95][96][97][98][99][100][101]…”
Section: A Brief Overview Of Photocatalysis Thermocatalysis and Photothermal Catalysismentioning
confidence: 99%
“…Photothermal CO 2 hydrogenation reactions can be powered synergistically by both heat and light from the sun [3] . This mechanism greatly broadens the effectual utilization range of the solar spectrum, especially the low‐energy infrared light often wasted in photochemical catalysis [4] . Therefore, absorbing in the entirety of the solar system is a key factor in achieving a high CO 2 conversion efficiency in catalytic processes.…”
Section: Figurementioning
confidence: 99%
“…In the past few years, many attempts have been made in the development of strong light absorptive catalysts. For example, several studies found that the light‐absorption ability can be enhanced by increasing the loading amount of metal nanoparticles [4–5] . We recently reported that MXene materials could serve as light absorptive supports to boost photothermal catalytic performance [6] .…”
Section: Figurementioning
confidence: 99%